2019
DOI: 10.1038/s41467-019-12839-6
|View full text |Cite
|
Sign up to set email alerts
|

Foxg specifies sensory neurons in the anterior neural plate border of the ascidian embryo

Abstract: Foxg constitutes a regulatory loop with Fgf8 and plays an important role in the development of anterior placodes and the telencephalon in vertebrate embryos. Ascidians, which belong to Tunicata, the sister group of vertebrates, develop a primitive placode-like structure at the anterior boundary of the neural plate, but lack a clear counterpart of the telencephalon. In this animal, Foxg is expressed in larval palps, which are adhesive organs with sensory neurons. Here, we show that Foxg begins to be expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(81 citation statements)
references
References 48 publications
3
78
0
Order By: Relevance
“…Using two-color, double in situ hybridization, we show that Nk4 is expressed at 7 hpf in the presumptive papilla territory, in both Foxg+ cells that give rise to the protuberances as well as Emx+/Foxg-negative cells that do not (Fig. 7 d–f) [ 61 ]. By 9 hpf, Nk4 appears to become a bit more spatially restricted to each papilla protuberance primordium (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using two-color, double in situ hybridization, we show that Nk4 is expressed at 7 hpf in the presumptive papilla territory, in both Foxg+ cells that give rise to the protuberances as well as Emx+/Foxg-negative cells that do not (Fig. 7 d–f) [ 61 ]. By 9 hpf, Nk4 appears to become a bit more spatially restricted to each papilla protuberance primordium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, it could also be that the expression of the above factors in the Ciona papilla lineage does not reflect evolutionary conservation of an ancestral myogenic gene regulatory network. ACC specification and differentiation is promoted by transcription factors like Islet and Foxg [ 61 , 113 ], which are not part of any myogenic CoRC. Since the contractility machinery assembled in the ACCs could result from various evolutionary co-options and convergences, this stresses the need for comprehensive studies comparing gene regulatory networks in more species and myogenic cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Though the ascidian embryos differ from the vertebrates and amphioxus, since the cells divide and select a fate based on their lineage instead of a field of equipotent cells exposed to diffusing morphogenetic cues, the row of cells at the dorsal-most non-neural ectoderm in the Ciona gastrula has been shown to express Six1/2, Pax3/7, and Msxb (Horie et al, 2018), some of the definitive markers for the vertebrate neural plate border ectoderm (reviewed in Schlosser et al, 2014;Thiery et al, 2020). Through lineage tracing experiments and cellular fate maps of Ciona, we know that the Six1 and Foxg cells contribute to the sensory organs like the palp adhesive organs and the oral siphon primordium (Mazet et al, 2005;Liu and Satou, 2019), whereas Msxb domain contributes to the bipolar tail neurons (Horie et al, 2018). FoxG1 transcription factor labels olfactory, optic, and otic placode in vertebrates (Hebert and McConnell, 2000;Duggan et al, 2008;Ermakova et al, 2019).…”
Section: Conservation Of Inductive Signals and Molecular Elements Of mentioning
confidence: 99%
“…Ascidian tadpoles also have ciliated primary sensory neurons in each of the palps, the anterior adhesive organs by which larvae appear to sense and bond to attachment sites [112,126]. Like aATEN cells, the palps develop from the area anterior to the neural plate postulated to be an olfactory/adenohypophyseal placode homologue and express many regulatory genes that are important for olfactory placode development in vertebrates, like Eya, COE, Dmrt, FoxC, FoxG, FGF, Sp8, Dlx and Isl [127][128][129][130]. It is possible that the palp sensory neurons are involved in tadpole settlement site selection via chemoreception, though again this is not experimentally validated and others have suggested that a different cell type in the palps may be chemosensory [121].…”
Section: Putative Olfactory Cell Homologues In Ascidiaceamentioning
confidence: 99%